Religion in the anthropocene - Deane-Drummond, Celia; Bergmann, Sigurd; Vogt, Markus (The Lutterworth Press, 2018)
This book charts a new direction in humanities scholarship through serious engagement with the geopolitical concept of the Anthropocene. Drawing on religious studies, theology, social science, history, philosophy, and what can be broadly termed the environmental humanities, this collection represents a groundbreaking critical analysis of diverse narratives on the Anthropocene. The contributors to this volume recognize that the Anthropocene began as a geological concept, the age of the humans, but that its implications are much wider than this. Will the Anthropocene have good or bad ethical outcomes? Does the Anthropocene debate trigger the emergence of a new ecological humanism? Does the Anthropocene idea challenge the possibility of a sacred Nature, which shores up many religious approaches to environmental ethics? Or is the Anthropocene a secularized theological anthropology more properly dealt with through traditional concepts from Catholic social teaching on human ecology? Do theological traditions, such as Christology, reinforce negative aspects of the Anthropocene? Not all contributors in this volume agree with the answers to these different questions. Readers will be challenged, provoked, and stimulated by this book